?SOME ASPECTS OF POPULATION DYNAMICS OF EXOPALAEMON STYLIFERUS FROM BANGLADESH COAST - Zafar, Mohammad; Mustafo, M G; Amin, SM Nurul (Biological Sciences - PJSIR, 2000)
Elefan I and Elefan II were used to estimate population parameters inExopalaemon styliferus from length-frequency data collected from Kutubdia channel of Bangladesh Coast. The L and K were 11.21em and 2.20 per year respec- tively. The annual rate of natural mortality, fishing and total mortality were 3.94, 4.57 and 8.57, respectively. The rate of exploitation (E) was 0.54. The mean length atfirst capture (Lc) was estimated as 6.276 cm. The shrimp was recruited in the fishery during March-May and July-October. Peak recruitment took place during April and Septem- ber. Emax was found0.859. This studyshowssomeover fishingofExopalaemon styliferus (E> 0.50) inthe Kutubdia Channel of Bangladesh coastal water. The length-weight relationship (W=0.00359TL 3184) was studied. The asymp- totic weight was calculated as 7.889g.